2017
DOI: 10.1080/21663831.2017.1323807
|View full text |Cite
|
Sign up to set email alerts
|

On the strain rate-dependent deformation mechanism of CoCrFeMnNi high-entropy alloy at liquid nitrogen temperature

Abstract: (2017) On the strain rate-dependent deformation mechanism of CoCrFeMnNi highentropy alloy at liquid nitrogen temperature, Materials Research Letters, 5:7, 472-477, DOI: 10.1080/21663831.2017 ABSTRACTIn the present work, the deformation mechanisms of the CoCrFeMnNi high-entropy alloy at 77 K were investigated using thermal activation analyses. The strain rate jump test was performed to estimate strain rate sensitivity and the activation volume of the alloy. Transmission electron microscopy analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…However, in ordered FCC phase (L1 2 ), dislocation glide (edge or screw or mixed) over obstacles is the dominant mechanism. The B2 phase showed a higher SRS than L1 2 phase, which is consistent with literature [37][38][39] . To evaluate the bulk response, overall SRS of the EHEA was determined at a load of 5 N at strain rates of 4 × 10 −2 s −1 , 1.2 × 10 −1 s −1 and 4 × 10 −1 s −1 .…”
Section: Small-scale Mechanical Behavior By Nano-indentationsupporting
confidence: 92%
“…However, in ordered FCC phase (L1 2 ), dislocation glide (edge or screw or mixed) over obstacles is the dominant mechanism. The B2 phase showed a higher SRS than L1 2 phase, which is consistent with literature [37][38][39] . To evaluate the bulk response, overall SRS of the EHEA was determined at a load of 5 N at strain rates of 4 × 10 −2 s −1 , 1.2 × 10 −1 s −1 and 4 × 10 −1 s −1 .…”
Section: Small-scale Mechanical Behavior By Nano-indentationsupporting
confidence: 92%
“…High-entropy alloys (HEAs) were first introduced in 2004 [1,2], which aimed to maximise the configuration entropy to form a single phase microstructure via combining four or more principle elements in equimolar or near equimolar ratios. The high configuration entropy, sluggish diffusion, cocktail effect and large lattice distortion lead to their promising properties such as high strength, excellent ductility, and superior fracture toughness [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One type of HEA and its variants, based on five 3d transition elements (Fe, Co, Cr, Mn, Ni), can form a single phase face-centered-cubic (fcc) structure, displaying an excellent combination of high strength, ductility and fracture toughness at both room and cryogenic temperatures. Their mechanical properties improve significantly with decreasing deformation temperatures [3][4][5][6][7]. We termed this group of HEA as tHEA to distinguish them from other high entropy alloys (such as multi-phase HEAs [8]).…”
Section: Introductionmentioning
confidence: 99%
“…For a high-entropy alloy, the lattice friction (Peierls stress) can be much higher than for a low alloy FCC metal due to its large lattice distortions, strong solid solution strengthening, and higher interaction energy between dislocations and solute atoms [27,28]. Hong et al [10] and Moon et al [9] have investigated the rate controlling mechanism of the CoCrFeMnNi alloy and reported that its activation volume for deformation is closer to that observed in BCC metals. The authors concluded that the high friction stress for dislocation motion to be the rate controlling mechanism in this alloy.…”
Section: Thermomechanical Analysismentioning
confidence: 98%
“…The authors also reported that its mechanical behavior was similar to those of materials with low stacking fault energy. Moon et al [9] and Hong et al [10] have studied the thermally activated deformation of a CoCrFeMnNi high entropy alloy at room and cryogenic temperatures, and have concluded that the rate controlling mechanism in this alloy is the overcoming of nanoscale obstacles such as short range orders (SROs) and clusters. However, the exact microstructural evolution and especially the high rate thermomechanical behavior of the alloy is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%